Marketing solutions to promote branding in eSports - Kalynets, Kateryna; Krykavskyy, Viktor (Technology audit and production reserves, 2022)
This study aims to identify marketing solutions that contribute to the improvement of brand image as a result of sponsorship participation in eSports. Since eSports is an activity that attracts millions of viewers worldwide, its development involves attracting sponsors and donors for its development. That is why marketing is a special tool that can promote this sport's endemic and non-endemic goods and services. The research aims to determine the special importance of eSports for promoting and selling goods and services advertised on virtual sports grounds. The object of the study is the influence of the brand's sponsorship participation in eSports tournaments on its image. A conceptual framework for the study was created and then refined with empirical data. This quantitative study analyzed 110 eSports fans who were selected using a non-probability heterogeneous method. Empirical data were collected through an online and closed-ended survey. Thus, more accurate and updated empirical data were collected to increase the conceptual framework's quality, reliability, and detail. In particular, special attention was paid to determining the subtleties that contribute to the improvement of the sponsors' brand image by the above-mentioned elements. The data showed that eSports sponsorship provides several main elements that enhance the sponsor's brand image. These elements include brand recognition, brand trust, building loyalty, referrals, willingness to try a new product, association with famous athletes. The field of eSports sponsorship is largely ignored by academia. As such, this study is first step in better understanding the benefits of eSports sponsorship and lays the groundwork for future research. Knowing the main brand image benefits of eSports sponsorship will help build confidence for brands that are still reluctant to enter this new market. Research has shown that the use of marketing strategy in eSports for brands of any scale corresponds to the stages of marketing strategy in traditional sports, in particular defining the target audience, and searching for channels of communication with the target audience, collaborating with celebrities, team sponsorship, holding an event with a white label.